RELASI FILOSOFIS ISLAM NUSANTARA DENGAN HINDU NUSANTARA DALAM HINDU TOLOTANG DI KABUPATEN SIDRAP SULAWESI SELATAN - Muhammad Alwi HS; Shofiyullah MZ; Zulfajri Amiruddin (Research and Development Center for Guidance for Religious Societies and Religious Services, the Research and Development and Education and Training Agency of the Ministry of Religious Affairs of the Republic of Indonesia (MORA), 2020)
This study aims to discuss the philosophical relation of the persecution and developing traditions in Islam Nusantara and Hindu Nusantara. This departs from the thesis that religious humans can not be separated from the tradition that encloses, even though the tradition does not make him satisfied in religion. This research is a field study, which describes as well as analyzing sources obtained from the results of interviews, observation, and documentation of the Hindu Tolotang group in Kelurahan Amparita Sidrap Regency, South Sulawesi. The results of this study say that Hindu Nusantara and Islam Nusantara are both able to finalize his teachings with the context of human life he encountered. The results of religious dialogue and contexts read in this study include tradition in the form of worship and social, visit the cemetery, marriage, pay promises or nazar, and respect for the leader or kiai. These four traditions show philosophical relation with each in its context. This shows that many traditions of marketing awakening in Islam and Hindu are maintained through Islam Nusantara initiated by the Nahdlatul Ulama and Hindu Nusantara initiated Hindu Tolotang. This article also shows that there is an understanding of Islam Nusantara and Hindu Nusantara which assesses the fact that Indonesia is a multicultural, pluralistic country that brings together religion and local culture.